How to build a library (Palíndromo, 2023)
The text presents the trajectory of just over a decade of Andante editions, a one-man-publishing company that operates independently and publish artists' books using different printing techniques. With examples of the creative process of some of his books, it points out how the job of editor can combine research and curatorship activities; that the experience in the classroom can influence artistic projects that, in turn, raise issues for debate in the classroom. The set of published books have certain common characteristics that allow us to understand them as part of an editorial project, as an artistic proposal that takes place over the years.
Keywords: independent publishing; artist-publisher; library